THE HOMOSEXUAL VICTIMS Of NAZISM AND THEIR PLACE IN A CULTURE Of REMEMBRANCE - Magda Borysławska (In Gremium. Studies in History, Culture and Politics, 2017)
The forgotten victims of Nazism are those, whose suffering was not acknowledged in the collective memory of a nation. The abovementioned category describes individuals persecuted on the ground of sexual orientation, both during the period of Third Reich and many years after its downfall. The research problem of the article is the approach towards the subject of gay persecution in the German historical narrative. The author performs an analysis of the reception of homosexual Nazism victims’ testimonies, taking into consideration political and ideological aspects of text refraction. The Polish memory discourse, in contrast to German discourse, rejects the issue of non-heteronormativity in the context of World War II history. It is demonstrated by, interalia, lack of memorial sites and marginalization of the subject in historical education.